Human papillomavirus genotypic characteristics of 60,685 subjects under age-expansion vaccination of the nine-valent human papillomavirus vaccine: A cross-sectional study - Yu Liu; Zhiqiang Li; Li Yuan; Fang Liu; Kailang Wu; Xuan Xiao; Chengliang Zhu (Elsevier, 2023)
Background: Human papillomavirus (HPV) vaccination is a key initiative to promote the WHO global strategy to accelerate the elimination of cervical cancer, and this study aimed to investigate the current status of HPV infection and genotypic characteristics of the population under the impact of age-expansion of nine-valent HPV vaccination policy in China. Methods: The clinical data of 60,685 subjects who were admitted in the Renmin Hospital of Wuhan University and underwent HPV genotyping from January 2017 to October 2022 were retrospectively analyzed. Results: The total number of positive HPV genotyping in the included population was 10,303, with a positivity rate of 17.0 %. The HPV positivity rate in the male and female populations increased slowly year by year, with a higher rate of positivity in men (32.7 %) than in women (16.7 %) (P < 0.001). HPV was predominantly single infection in all populations, with higher prevalence of high-risk HPV than low-risk HPV in females, while low-risk HPV infection was predominant in the male population. The age distribution of female subjects infected with HPV, with HPV52 as the most common type, showed a bimodal pattern. As for HPV infected male subjects, HPV6 was the main type, and there was no bimodal age distribution. The expanded age vaccination of the nine-valent HPV vaccine will result in 42.4 % efficiency of vaccine protection for 49.9 % of age-eligible women. If the nine-valent HPV vaccine were open to males in China, it would reduce HPV infections in men by 56.4 %. Conclusions: The HPV positivity rate in the population remains high and tends to increase, and the age-expansion of the nine-valent HPV vaccine would contribute to reducing the threat of disease caused by HPV infection for age-eligible women. Moreover, attention should be paid to enhancing HPV screening in males and opening up vaccination when appropriate.